2003
DOI: 10.1084/jem.20030357
|View full text |Cite
|
Sign up to set email alerts
|

A Fail-safe Mechanism for Negative Selection of Isotype-switched B Cell Precursors Is Regulated by the Fas/FasL Pathway

Abstract: In B lymphocytes, immunoglobulin (Ig)M receptors drive development and construction of naive repertoire, whereas IgG receptors promote formation of the memory B cell compartment. This isotype switching process requires appropriate B cell activation and T cell help. In the absence of T cell help, activated B cells undergo Fas-mediated apoptosis, a peripheral mechanism contributing to the establishment of self-tolerance. Using Igμ-deficient μMT mouse model, where B cell development is blocked at pro-B stage, her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…Another mechanism of negative selection is apoptosis, mediated via Fas/ Fas ligand interaction. We have recently shown that the Fas pathway is important for blocking the development of autoimmune isotype-switched B cell precursors in the BM [54,61]. Since stimulation with CpG DNA protects B cells against Fas-mediated apoptosis by downregulating Fas expression [62], it may allow isotypeswitched B cell precursors to escape this deletion and to construct an autoimmune repertoire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another mechanism of negative selection is apoptosis, mediated via Fas/ Fas ligand interaction. We have recently shown that the Fas pathway is important for blocking the development of autoimmune isotype-switched B cell precursors in the BM [54,61]. Since stimulation with CpG DNA protects B cells against Fas-mediated apoptosis by downregulating Fas expression [62], it may allow isotypeswitched B cell precursors to escape this deletion and to construct an autoimmune repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most of the antibodies produced by BM B cells are low-affinity and nonpathogenic IgM isotype [3]. However, studies have shown that developing B cells can undergo somatic hypermutation and class switch recombination [54,55], which suggests a mechanism by which high-affinity effector antibody can be generated. (iii) An alternative possibility is that activation occurs outside the BM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, IgG/IgA-secreting CD19 high CD45R Ϫ/low spleen cells could be a physiological correlate of the distinct developmental pathway to IgG-and IgA-switched B cells described in Ig-deficient mice, which is established at the level of B cell precursors and is T independent (43,44). Although not induced by intentional immunization, the IgG/IgA production of the CD19 high CD45R Ϫ/low B cells might be the result of regular microbial encounters (45), particularly, intestinal bacteria, but these cells also contributed importantly to the early postnatal IgG production, which is known to be developmentally controlled and (foreign) Ag independent (46).…”
Section: Cd45rmentioning
confidence: 99%
“…Serum IgG is also present in CD40/CD40L-deficient mice (38) and in patients with X-linked hyper-IgM syndrome (39). CSR can occur in responses to thymusindependent Ags (40) and TLR ligands (18,41) and during B cell lymphogenesis independently of T cells (42,43). Furthermore, both CSR and somatic hypermutation can occur outside of germinal centers (44).…”
mentioning
confidence: 99%